2016
DOI: 10.17245/jdapm.2016.16.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of dexmedetomidine (DEX) as a premedication for pediatric patients undergoing general anesthesia for dental treatment

Abstract: BackgroundThe most important reason for pre-operative administration of medication is to reduce anxiety. Alleviation of fear and anxiety about surgery enables patients to remain comfortable during treatment. Dexmedetomidine (DEX) is a fast-acting drug that is used as a premedication in different circumstances because it has sedative and anti-anxiolytic effects, and stable hemodynamics. It also has the advantage of intranasal administration. The aim of this study was to investigate the effects and hemodynamic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“… 9 10 However, dexmedetomidine, like most potent sedatives, causes an unpleasant burning sensation when applied intranasally. 11 Oral application might therefore be a better choice for anxious children. One recent study showed that 1 µg/kg oral dexmedetomidine for premedication provided satisfactory sedation levels, but was not effective in preventing ED.…”
Section: Discussionmentioning
confidence: 99%
“… 9 10 However, dexmedetomidine, like most potent sedatives, causes an unpleasant burning sensation when applied intranasally. 11 Oral application might therefore be a better choice for anxious children. One recent study showed that 1 µg/kg oral dexmedetomidine for premedication provided satisfactory sedation levels, but was not effective in preventing ED.…”
Section: Discussionmentioning
confidence: 99%
“…11 Additionally, dexmedetomidine (DEX), a fastacting drug, is administered as a premedication in various situations due to its sedative and antianxiolytic effects and stable hemodynamics. 12 A series of findings have demonstrated that DEX could alleviate brain damage in neonatal rats following brain hypoxia-ischemia due to mediation of the α2 receptor to inhibit the inflammation in ischemic brain tissue. 13 Moreover, DEX exerts its protective effects during the treatment of cerebral ischemia and for recovering from hypoxia-ischemia-induced neuronal cell injury.…”
Section: Introductionmentioning
confidence: 99%
“…Two published studies could show a reduction of incidence and degree of ED following premedication with intranasal dexmedetomidine 9 10 . However, dexmedetomidine, like most potent sedatives, causes an unpleasant burning sensation when applied intranasally 11 . Oral application might therefore be a better choice for anxious children.…”
Section: Discussionmentioning
confidence: 99%